Design and analysis of metacarpophalangeal joint to relieve pain due to osteoarthritis [electronic resource] - 182163 Muhammad Azuwan Aminullah (2008)
Project Paper (Sarjana Muda Kejuruteraan (Mekanikal - Bahan)) - Universiti Teknologi Malaysia, 2008